Self Assessment of FKIP Univet Bantara Lecturer - Meidawati Suswandari; Erika Laras Astutiningtyas; Annisa Prima Exacta; Isna Farahsanti (Jurnal Pendidikan Edutama, 2023)
Abstract: The purpose of this research is to find out Self assessment of FKIP Lecturer, Universitas Veteran Bangun Nusantara The method used in this research is a survey. Survey data is collected using a questionnaire. The population is aimed at lecturers in 11 study programs and PPG in the FKIP Univet Bantara Sukoharjo as many as 89 lecturers. The research samples consisted of 46 lecturers who are spreaded from 11 FKIP and PPG study programs. The sampling technique in self-assessment is cluster sampling. The measurement of the self-assessment survey for lecturers in the 2021/2022 academic year uses the Likert scale. Analysis of research data uses scale criteria based on Permendikbud No. 81 A of 2013. The results obtained from this survey research are self-assessment of lecturers in charge of courses in the FKIP Univet Bantara environment in the Good category with a percentage above 80%. This self-assessment builds lecturers' knowledge in planning and monitoring developments in terms of strengths and weaknesses, both between lecturers and students in achieving learning objectives. Keywords: Self assessment, course, study program  Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui self assessment dari dosen FKIP Universitas Veteran Bangun Nusantara. Metode yang digunakan dalam penelitian ini adalah metode survei. Pengumpulan data survey menggunakan kuesioner. Populasi ditujukan pada dosen yang ada di 11 program studi dan PPG di lingkungan FKIP Univet Bantara Sukoharjo sejumlah 89 dosen. Sampel penelitian sejumlah 46 dosen yang tersebar dari 11 program studi FKIP dan PPG. Teknik pengambilan sampel dalam self assessment yaitu cluster sampling. Pengukuran survey self assesment dosen pengampu mata kuliah tahun akademik 2021/2022 menggunakan skala likert. Analisisi data penelitian memakai kriteria skala berdasarkan Permendikbud No.81 A Tahun 2013. Hasil yang diperoleh dari penelitian survey ini yaitu self assesment dosen pengampu mata kuliah di lingkungan FKIP Univet Bantara dalam kategori Baik dengan persentase di atas 80%. Self assessment ini membangun pengetahuan dosen dalam merencanakan dan memantau perkembangan secara kelebihan maupun kekurangan kemampuan, baik antara dosen maupun mahasiswa dalam mencapai tujuan pembelajaran. Kata Kunci: penilaian diri, mata kuliah, program studi